LONG-TERM RESULTS OF AUTOLOGOUS RETINAL PIGMENT EPITHELIUM AND CHOROID TRANSPLANTATION FOR THE TREATMENT OF EXUDATIVE AND ATROPHIC MACULOPATHIES. Issue 3 (March 2020) - Parolini, Barbara; Di Salvatore, Attilio; Pinackatt, Sajish Joseph; Baldi, Andrea; Besozzi, Gianluca; Finzi, Alessandro; Cardillo, Daniele; Sallam, Ahmed B.; Frisina, Rino
Abstract : Purpose: To evaluate the long-term results of autologous retinal pigment epithelium (RPE) and choroid transplantation (RPE–choroid patch) for exudative and atrophic maculopathies. Methods: Consecutive chart review of 120 eyes, which underwent RPE–choroid patch, from 2007 to 2017 for RPE atrophy or choroidal neovascular membrane secondary to exudative and hemorrhagic age-related macular degeneration, myopia, angioid streaks, and laser. Eyes were tested with best-corrected visual acuity (BCVA), reading ability, optical coherence tomography, fluorescein angiography and indocyanine green angiography, autofluorescence, and microperimetry. Results: Eighty-eight eyes of 84 patients had complete data, with 2- to 10-year follow-up. Mean age was 71.9 ± 9.06 years. Mean preoperative and postoperative BCVA was 20/320 (1.2 ± 0.2 logMAR) and 20/200 (0.94 ± 0.36 logMAR), respectively ( P = 0.009). Reading ability recovered in 43% of cases. Microperimetry showed central fixation. A gain of at least 15 letters was obtained in 40% of eyes. Integrity ( P = 0.009) of external limiting membrane and higher preoperative BCVA ( P = 0.001) predicted better final BCVA. Complications were retinal detachment (11.4%), macular atrophy (7%), subretinal hemorrhage (4.5%), epiretinal membrane (4.5%), recurrent choroidal neovascular membrane (4.5%), macular hole (3.4%), and cystoid edema (3%). Conclusion: Autologous RPE–choroid patch achieved long-lasting BCVA improvement and central fixation, in eyes with choroidal neovascular membrane and intact external limiting membrane. Atrophic maculopathies only obtained temporary visual benefit. Abstract : Anatomical–functional results, prognostic factors, and complications of retinal pigment epithelium–choroid transplantation, in 88 eyes with exudative and atrophic maculopathies, followed up for 2 to 10 years. Best-corrected visual acuity improved significantly. Reading ability recovered in 43%. External limiting membrane integrity and higher preoperative best-corrected visual acuity were predictive of better final best-corrected visual acuity.